Impact of Financial Leverage on Firm’s Profitability: Evidence from Chemical Sector of Pakistan - MUHAMMAD KAMRAN; KASHIF ROSE; WAHID ULLAH; MATIULLAH (Journal of Business & Tourism, 2021)
The purpose of this study to investigated the impact of financial leverage on firm’s profitability by taking a sample of 24 firms in chemical sector that are registered in Pakistan Stock Exchange and data were collected from annual reports of the firms for the year 2010 to 2015. Financial leverage used as explanatory variable and firm’s profitability used as a response variable. Further the explanatory was measured by debt to equity ratio, debt ratio, shortterm debt ratio and response variable was measured by return on equity ratio (ROA) and return on equity (ROE). In first model debt to equity ratio has positive but insignificant association with ROA. The debt ratio has negative but significant relationship with return on assets. The short-term debt ratio has negative and insignificant relationship with return on asset. A result shows the debt ratio has significant impact on firm’s profitability of chemical sector of Pakistan. Negative and significant relationship of debt ratio with firm profitability shows that if firm increases its debt level then firm’s profitability level will decrease. This indicates that there is some inverse relationship between debt and firm’s profitability. But in second model, it is concluded that debt to equity ratio has negative but significant association with return on equity. The debt ratio has positive but significant relationship with return on equity. The short-term debt ratio has negative and insignificant relationship with return on equity. So, model two indicates that D/E ratio negatively affect the ROE while debt ratio positively affect the ROE it means that if firm increase debt proportion then firm profitability increases